Binding interaction of a prospective chemotherapeutic antibacterial drug with β-lactoglobulin results and challenges - Paul, Bijan K (Langmuir : the ACS journal of surfaces and colloids, 2014)
This Article reports a detailed characterization of the binding interaction of a potential chemotherapeutic antibacterial drug, norfloxacin (NOF), with the mammalian milk protein β-lactoglobulin (βLG). The thermodynamic parameters, ΔH, ΔS, and ΔG, for the binding phenomenon as-evaluated on the basis of van't Hoff relationship reveal the predominance of electrostatic/ionic interactions underlying the binding process. However, the drug-induced quenching of the intrinsic tryptophanyl fluorescence of the protein exhibits intriguing characteristics on Stern-Volmer analysis (displays an upward curvature instead of conforming to a linear regression). Thus, an extensive time-resolved fluorescence spectroscopic characterization of the quenching process has been undertaken in conjugation with temperature-dependent fluorescence quenching studies to unveil the actual quenching mechanism. The invariance of the fluorescence decay behavior of βLG as a function of the quencher (here NOF) concentration coupled with the commensurate dependence of the drug-protein binding constant (K) on temperature, the drug-induced fluorescence quenching of βLG is argued to proceed through static mechanism. This postulate is aided further support from absorption, fluorescence, and circular dichroism (CD) spectral studies. The present study also throws light on the important issue of drug-induced modification in the native protein conformation on the lexicon of CD, excitation-emission matrix spectroscopic techniques. Concurrently, the drug-protein interaction kinetics and the energy of activation of the process are also explored from stopped-flow fluorescence technique. The probable binding locus of NOF in βLG is investigated from AutoDock-based blind docking simulation